Detection of Onset of Melt and Freeze of Snow in the Upper Chenab Basin Using Remote Sensing Data - A. Santhosh; V. Garg; P. K. Thakur (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Snow cover and its changes play a significant role in influencing hydrological and climate processes. Each year, approximately one-third part of the land surface of earth undergoes seasonal snow coverage, highlighting its significant role as one of the most dynamic components of the cryosphere, alongside sea ice. In the cryosphere studies, identifying the onset and progression of snow accumulation and ablation is of utmost importance and critical significance. The present work highlights the importance of remote sensing (RS) data in detection and monitoring of melt and freeze of snow in different elevation zones in the Upper Chenab basin using synthetic aperture radar and albedo data along with temperature data . The detection of onset of melt and freeze of snow was carried out from 2015 to 2023. The optimal value for threshold was identified empirically by comparing air temperature time series data. The time series analysis of backscatter values and albedo values clearly depicts the melt and freeze of snow. As the surface air temperature increases above a particular value, there observed a consistent decrease in backscatter /albedo response. A short time delay in change in backscatter, albedo and temperature with the different elevation zones. As the temperature increases, the glacier starts melting and the water content increases, so the backscatter and albedo decreases and hence on the melting period the backscatter will be low and vice versa. Overall, the onset of melt of the snow will occur early in the lower elevation zone compared to the higher elevation zone. And the onset of freeze will occur early in the higher elevation zone compared to the lower elevation zone.